Effect of Topical Anti-Glaucoma Medications on Late Pupillary Light Reflex, as Evaluated by Pupillometry - Ba-Ali, Shakoor; Sander, Birgit; Brøndsted, Adam Elias; Lund-Andersen, Henrik (Frontiers in Neurology, 2015)
Purpose: The late post-illumination pupillary response (PIPR10-30s) to blue light is reduced in glaucoma, suggesting that pupillometry can be used in clinical glaucoma evaluation. Since animal studies have indicated that common anti-glaucomatous agents affect the iris muscle, we investigated the short term effect of the antiglaucoma drugs on the pupillary light reflex and in particular on the PIPR10-30s. Methods: In this randomized, double-masked, crossover trial, pupillometry was performed before and after topical administration of latanoprost, dorzolamide and timolol in 20 healthy subjects. Stimulus was blue- (463 nm) and red light (633 nm) of 2 log (lux). Main outcome was the PIPR10-30s to blue light. Additionally, pupil size, maximal contraction and the early post-illumination pupillary response (PIPR0-10s) to blue- and red light were investigated. Pupil response variations between 8 AM and 2 PM were also assessed. IOP was measured before and 3.5 h after drug instillation. Results: We found no drug effect on the blue light PIPR10-30s or any other blue light pupil parameters. During the control day, the only significant variation over time was observed for the red light PIPR0-10s (p = 0.02). Pupillary size decreased slightly with timolol (0.1 mm, p = 0.03) and dorzolamide (0.2 mm, p < 0.001), but not with latanoprost. Timolol also reduced the maximal contraction amplitude significantly during red light (p = 0.02). IOP was significantly reduced by all three drugs after 3.5 hours (p < 0.01), while it remained unchanged during the control day (p = 0.3). Conclusion: Antiglaucoma medications did not interfere with the blue light elicited PIPR. Dorzolamide reduced pupil size, while timolol reduced both pupil size and maximal contraction to red light, but the effect was minute and not of clinical importance.